Paracoccidioidomycosis: level of pulmonary sequelae in high resolution computed tomography images from patients of two endemic regions of Brazil - Pina, Diana Rodrigues de [UNESP]; Alvarez, Matheus [UNESP]; Giacomini, Guilherme [UNESP]; Menegatti Pavan, Ana Luiza [UNESP]; Andrade Guedes, Carlos Ivan; Cavalcante, Ricardo de Souza [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Miranda Paniago, Anamaria Mello (Ame Publ Co, 2017)
Background: The purpose of the present study was to evaluate differences in lung damage in patients with paracoccidioidomycosis (PCM) in two endemic regions of Brazil (Botucatu, SP, in the southeastern region and Campo Grande, MS, in the west central region). Methods: The study sought to objectively quantify fibrosis and emphysema treated patients using high-resolution computed tomography (HRCT) that was performed according to an established and validated computational method. The analysis was based on clinical data that were associated with objective quantifications of pulmonary sequelae. We performed a retrospective analysis of HRCT exams from 32 successfully treated patients with the chronic form of PCM. The two groups had similar characteristics with regard to age, symptom duration, smoking history, and titers on a diagnostic serologic test. Results: The statistical analysis revealed more severe cases and a higher percentage of emphysema in the Campo Grande group. The mean percentages of emphysema were 40.2% and 13.6% in the Campo Grande and Botucatu groups, respectively. The percentage of fibrosis was significantly higher in the Botucatu group (11.3%) than in the Campo Grande group (2.3%). Conclusions: The present results may reflect differences in cryptic species of P. brasiliensis in these two geographic regions of Brazil. Further studies should be done to clarify the differences observed herein. Such findings may help unveil differences among cryptic species in terms of the pulmonary consequences that are caused by this disease, which would be highly beneficial to PCM patients.
Keywords: Cryptic species; emphysema; fibrosis; paracoccidioidomycosis (PCM); quantification; tissue